The Assessment Tool Of L2 Learners' Pragmatic Competence: Written Discourse Completion Test (WDCT) - Aufa, Fauzul (Journal of English and Education (JEE), 2012)
Research studies have shown that pragmatic competence is teachable. The importance of teaching pragmatics has also been recognized, but still foreign language teachers are reluctant to teach pragmatics in their classrooms. This might be partly due to the lack of some valid methods for assessing pragmatic competence. This essay contends that while the Written Discourse Completion Test (WDCT) has some pitfalls, the WDCT effectively assesses learner's pragmatic competence.Key words: pragmatic competence, teaching pragmatics, pragmatic competence assessments, Written Discourse Completion Test (WDCT)